Gelatinases-stimuli nanoparticles encapsulating 5-fluorouridine and 5-aza-2′-deoxycytidine enhance the sensitivity of gastric cancer cells to chemical therapeutics. Issue 1 (10th July 2015) - Wu, Feng-lei; Li, Ru-Tian; Yang, Mi; Yue, Guo-Feng; Wang, Hui-yu; Liu, Qin; Cui, Fang-bo; Wu, Pu-yuan; Ding, Hui; Yu, Li-Xia; Qian, Xiao-Ping; Liu, Bao-Rui
Highlights: The use of intelligent gelatinases-stimuli nanoparticles to deliver 5-aza-2′-deoxycytidine and 5-fluorouridine to gastric cancer cells. The intelligent gelatinases-stimuli nanoparticles enhanced the stability of 5-aza-2′-deoxycytidine. Incorporating 5-aza-2′-deoxycytidine into NPs significantly enhanced the sensitivity of gastric cancer cells to 5-fluorouridine. Abstract: Aberrant methylation of the transcription factor AP-2 epsilon (TFAP2E) has been attributed to 5-fluorouridine (5-FU) sensitivity. 5-Aza-2′-deoxycytidine (DAC), an epigenetic drug that inhibits DNA methylation, is able to cause reactive expression of TFAP2E by demethylating activity. This property might be useful in enhancing the sensitivity of cancer cells to 5-FU. However, the effect of DAC is transient because of its instability. Here, we report the use of intelligent gelatinases-stimuli nanoparticles (NPs) to coencapsulate and deliver DAC and 5-FU to gastric cancer (GC) cells. The results showed that NPs encapsulating DAC, 5-FU, or both could be effectively internalized by GC cells. Furthermore, we found that the NPs enhanced the stability of DAC, resulting in improved re-expression of TFAP2E. Thus, the incorporation of DAC into NPs significantly enhanced the sensitivity of GC cells to 5-FU by inhibiting cell growth rate and inducing cell apoptosis. In conclusion, the results of this study clearly demonstrated that the gelatinases-stimuli NPs are an efficient means to simultaneously deliver epigenetic and chemotherapeutic drugs that may effectively inhibit cancer cell proliferation.